Dan's days aged 7 : (being a week of his words) - "Flavell, Adrian" (Hawthorn; Mimosa/McGraw-Hill, 2007)
A week in the life of Dan. He's seven years old and has to deal with family, school and wanting to be invited to the cool kid Sean's birthday party
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Humorous fiction